State disparities in colorectal cancer rates: Contributions of risk factors, screening, and survival differences - Lansdorp_Vogelaar, Iris; Goede, S.; Ma, J.; Xiau-Cheng, W.; Pawlish, K.; Van Ballegooijen, M.; Jemal, A. (John Wiley & Sons, Inc., 2015)
BACKGROUND Northeastern states of the United States have shown more progress in reducing colorectal cancer (CRC) incidence and mortality rates than Southern states, and this has resulted in considerable disparities. This study quantified how the disparities in CRC rates between Louisiana (a Southern state) and New Jersey (a Northeastern state) would be affected if differences in risk factors, screening, and stage-specific CRC relative survival between the states were eliminated. METHODS This study used the Microsimulation Screening Analysis Colon microsimulation model to estimate age-adjusted CRC incidence and mortality rates in Louisiana from 1995 to 2009 under the assumption that 1) Louisiana had the same smoking and obesity prevalence observed in New Jersey, 2) Louisiana had the same CRC screening uptake observed in New Jersey, 3) Louisiana had the same stage-specific CRC relative survival observed in New Jersey, or 4) all the preceding were true. RESULTS In 2009, the observed CRC incidence and mortality rates in Louisiana were 141.4 cases and 61.9 deaths per 100,000 individuals, respectively. With the same risk factors and screening observed in New Jersey, the CRC incidence rate in Louisiana was reduced by 3.5% and 15.2%, respectively. New Jersey's risk factors, screening, and survival reduced the CRC mortality rate in Louisiana by 3.0%, 10.8%, and 17.4%, respectively. With all trends combined, the modeled rates per 100,000 individuals in Louisiana became lower than the observed rates in New Jersey for both incidence (116.4 vs 130.0) and mortality (44.7 vs 55.8). CONCLUSIONS The disparities in CRC incidence and mortality rates between Louisiana and New Jersey could be eliminated if Louisiana could attain New Jersey's levels of risk factors, screening, and survival. Priority should be given to enabling Southern states to improve screening and survival rates.